Dedicated Spine Trauma Clinical Quality Registries: A Systematic Review - Tee, Jin W. (Georg Thieme Verlag KG, 2013)
Study Design Systematic review. Objective We assessed the current state of spine registries by collecting spine trauma data and assessing their compliance to defined registry standards of being clinical quality. We ascertained if these registries collected spinal cord injury data alone or with spine column trauma data. Methods A systematic review was performed using MEDLINE and Embase databases for articles describing dedicated spinal cord and spine column databases published between January 1990 and April 2011. Correspondence with these registries was performed via e-mail or post. When no correspondence was possible, the registries were analyzed with best information available. Results Three hundred eight full-text articles were reviewed. Of 41 registries identified, 20 registries fulfilled the criteria of being clinical quality. The main reason for failure to attain clinical quality designation was due to the unavailability of patient outcomes. Eight registries collected both spine column and spinal cord injury data with 33 collecting only traumatic spinal cord injury data. Conclusion There is currently a paucity of clinical quality spine trauma registries. Clinical quality registries are important tools for demonstrating trends and outcomes, monitoring care quality, and resolving controversies in the management of spine trauma. An international spine trauma data set (containing both spinal cord and spine column injury data) and standardized approach to recording and analysis are needed to allow international multicenter collaboration and benchmarking.